(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Modern technology, particularly the internet revolution, has greatly improved the quality of human life. As it has been said that every coin has two sides, so are security lapses making people more open to assault, one of which can be triggered or initiated through a keylogger. In this paper Keyloggers, various keylogger types are discussed. Keyloggers are one of the notable tools that can be used to gather sensitive or private information from both legitimate and contradictory malicious users too. These keyloggers are extremely advantageous and are used positively for monitoring employee productivity, for law enforcement and the search for evidence of the crime, while it’s negative illegal use includes data theft and passwords. Software keyloggers that may be simply distributed through email as an attachment or via a link to play or watch a movie, etc. makes the users vulnerable. Keyloggers can remain undetected while capturing keystrokes and sending the details to hackers for planning and executing attack.